Analysis of ecological systems : state-of-the-art in ecological modelling : proceedings of a symposium held from 24 to 28 May 1982 at Colorado State University, Fort Collins, Colorado, U.S.A. - Lauenroth, William K.; Skogerboe, Gaylord V.; Flug, Marshall (Developments in environmental modelling, 1983)
The International Society for Ecological Modelling (ISEM) sponsors conferences, workshops and training courses with the aim of advancing the development of ecological and environmental modelling. The 3rd International Conference on the state-of-the-art in ecological modelling was sponsored by the ISEM in cooperation with the National Park Service Water Resources Laboratory and hosted by the Natural Resource Ecology Laboratory at Colorado State University. Its theme was the application of ecological modelling to environmental management and this book contains the full texts of the three invit.